2011
DOI: 10.1002/jssc.201000856
|View full text |Cite
|
Sign up to set email alerts
|

Separation of inorganic anions on a triazole‐functionalized ion exchanger in ion chromatography

Abstract: The retention behavior of inorganic anions on a triazole-based stationary phase was first examined in ion chromatography. It was initially designed for hydrophilic interaction liquid chromatography and was simply prepared by introducing the triazole groups onto the surface of silica gel via click chemistry. Effective separation of common inorganic anions, including iodate, chloride, bromide, nitrate and iodide, was achieved with Na(2)SO(4) eluent. The logarithm of the retention factor of analytes was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…29 While its drawback was limited effective anion capacity (column, 4.6 mm i.d. Â 150 mm long, 2.67 mmol column À1 ).…”
Section: Chromatographic Evaluation Of Ctasp Under Ic Modementioning
confidence: 99%
See 3 more Smart Citations
“…29 While its drawback was limited effective anion capacity (column, 4.6 mm i.d. Â 150 mm long, 2.67 mmol column À1 ).…”
Section: Chromatographic Evaluation Of Ctasp Under Ic Modementioning
confidence: 99%
“…As indicated previously, the protonated triazole ring or trapped eluent cation served to be ion exchange sites. 29 Herein the eluent of 5 mM Na 2 SO 4 + 0.5 mM H 2 SO 4 and 5 mM Na 2 SO 4 were used to evaluate the retention of the analytes, respectively, as provided in support information SI- Fig.3. † The results show that the retention of five model anions slightly increased with the decrease of the eluent pH value, indicating that the pH value of the eluent has less of an effect on the retention of the analytes.…”
Section: Chromatographic Evaluation Of Ctasp Under Ic Modementioning
confidence: 99%
See 2 more Smart Citations
“…However, the triazole groups in the immobilized state have been proven to carry positive charge [31]. Recently, Zhang et al further confirmed this point by the experiment that a triazole-based stationary phase was used to separate inorganic anions by ion chromatography mode [32]. In this work, the z-potential values of poly(HTMA)-grafted beads (column C) were determined to be 11.4, 9.9, 8.3 and 4.7 mV in 20 mM ammonium formate at pH 3.0, 5.0, 7.0 and 8.0, respectively, whereas the z-potential of unmodified beads was in the range of À1.2 to À0.5 mV at the investigated pH range.…”
Section: Retention Behavior Of Poly(htma)-grafted Stationary Phasementioning
confidence: 99%